Identita(y) obyvatel tádžického Pamíru - Tomáš Retka (AntropoWebzin, 2010)
The aim of the text is to point out to the concept of identity (eventually identities) of the inhabitants of Tajik part of the Pamir – so-called Pamirs. The author acquired the data mentioned in the text during his fieldwork in the Republic of Tajikistan in the year 2006. The data and the working conclusions were elaborate in author´s diploma thesis. The author poses himself a question about the essence of identity (or identities) of the Tajik Pamirs. To find the answer to such a question he uses a theoretical concept base on the assumption, that the principal feature of any identity is contrast, dissimilarity or divergence to the Others (so to the non-members of the group) (Bauman 1996, Eriksen  2007). Tajik Pamirs differentiate from the other inhabitants of the Republic of Tajikistan mostly by their language, religion and in some aspects also by material culture. We can understand those three aspects as main sources of so-called Pamir´s identity. The belonging to the group so-called Pamirs is then demonstrated mainly in a symbolical level through stereotypes. The author point out to a multi-level essence of the phenomenon of defining oneself towards the other. It is possible to understand such defining not only as a certain manifestation of the identity, but in certain circumstances also as the source of the identity.  The article is concerned on a description of the main sources of the Pamir´s identity and on an analysis of the ways, how this phenomenon can be manifested in the different social contexts. The author points out that there are also other aspects of the problematic of the Pamir´s identity (or partial identities) that need to be put through the further intensive fieldwork in the locality. So, in up to date state of the research the aim of the text is not to make up generalisations or social theories, but to offer the approach how can be delt with this problematic. The author presupposes another fieldwork in this locality that could help to find the answer to the new questions that appeared during the work on the topic.